2013
DOI: 10.2166/wp.2013.160
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of household participation in the management of rural water supply systems: A case from Ethiopia

Abstract: Access to safe drinking water supply in Ethiopia is among the lowest in sub-Saharan Africa. While both governmental and non-governmental organizations have implemented water supply projects in recent years, many fail shortly after construction due to improper management. In this paper, we examine socio-economic, institutional and exogenous factors affecting household participation in the management of water supply systems for drinking purposes. A survey was carried out involving 16 water supply systems and 160… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Jurisdiction over water resources and/or water-related services delivery might be contested by these groups. Socio-economic conditions of participants: Evidence suggest a correlation between the success of participatory approaches and the prevailing socio-economic wealth of a society [120,125,126], and of households [127]; while other scholars show that participants in community-based activities are generally more educated or well-off [119,125,128]. Social norms and practices around use of water: One-fit-for-all solution does not work [59].…”
Section: Supportive Institutional Frameworkmentioning
confidence: 99%
“…Jurisdiction over water resources and/or water-related services delivery might be contested by these groups. Socio-economic conditions of participants: Evidence suggest a correlation between the success of participatory approaches and the prevailing socio-economic wealth of a society [120,125,126], and of households [127]; while other scholars show that participants in community-based activities are generally more educated or well-off [119,125,128]. Social norms and practices around use of water: One-fit-for-all solution does not work [59].…”
Section: Supportive Institutional Frameworkmentioning
confidence: 99%
“…Some authors observed that the lack of institutional support and political planning are major contributors to systems' failures, as seen in Ghana [5] and Nigeria [12]. Insufficient financial resources and weak tariff schemes also have been recognized as leading causes of failure of rural water services [8,[13][14][15]. Additionally, several studies identified maintenance issues as critical to the functionality of community-managed systems, such as the execution of insufficient preventive repairs [16], difficulties to obtain spare parts [12] and lack of technical support from external entities [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…However, the inclusion of temperature as an additional impact variable has no significant effect on water demand. Tigabu (2016) estimated the water service management determinants at the household level. The findings revealed that the provision of sustainable water supply leads to increase in the household participation in water management.…”
Section: Literature Reviewmentioning
confidence: 99%